Effective Structural System for the Affordable Housing Construction - Pavlikov, Andrii; Mykytenko, Serhii; Hasenko, Anton (International Journal of Engineering and Technology, 2018)
This article falls within vital question in quickly builds construction â€“ theoretical method for calculating the slabs and columns of such buildings. Calculation research of buildings with reinforced concrete frame slabs is described in the article. The features of work the collapsible flat plate ceiling in composition of reinforced concrete framework of building are analyzed. Problems in the design of framework building are considered in order to increase its reliability. The suggestions for directions of perfection the calculation of flat plate frame construction elements are proposed in the article. The novelty of this work is to get new theoretical data about bearing capacity and deformability of structural system for the affordable housing construction from reinforced concrete.Â Â